Early Marriage in The Perspective of Fikih and Positive Law Between Textual and Contextual Islamic Family Law in Indonesia - Muhammad Hatami (ASTEEC, 2025)
Early marriage is one of the important issues in Islamic family law in Indonesia because it involves a tug-of-war between textual and contextual views of Sharia law. On the one hand, classical fiqh legitimizes marriage before adulthood by using puberty as a benchmark for readiness to marry, and bases its arguments on historical practices such as the marriage of the Prophet Muhammad to Aisha. On the other hand, contemporary social dynamics show that early marriage often causes harm, such as mental unpreparedness, reproductive health risks, divorce, and economic instability. This study uses a normative legal research method with a comparative approach, through a literature review of fiqh books, contemporary literature, the Qur'an and hadith, as well as legal documents such as the UUP and KHI. The results of the study show that the differences between the textual and contextual groups produce contrasting legal interpretations. The textual view emphasizes the validity of classical practices and does not impose restrictions on the age of marriage, while the contextual view emphasizes maqāṣid al-syarī‘ah, public interest, and social change, thereby encouraging minimum age restrictions as a means of protecting children and families. Indonesian positive law is in line with the contextual approach by strictly regulating age limits and dispensations.